Intelligent voltage regulator for distributed generation-based network - Zwawi Hamadouche; Mounir Khiat; Muhammad Asad Iqbal (Institute of Advanced Engineering and Science, 2021)
Power grids are being transformed into a smart distribution network that incorporates multiple distributed energy resources (DERs), ensuring stable operation and improved power quality at the same time. Many research papers have been published in recent years that discuss the voltage violation issues that emerge from the high penetration of distributed generation (DG). In this paper, we propose a new optimal voltage control technique based on feedforward neural networks (FFNN) to maintain a stable voltage profile. MATLAB®/Simulink® has been used to carry out the simulation. The simulation results show the efficiency of this method in voltage control. The proposed approach ensured a stable voltage profile for the considered schemes.